Rediscovery of Crucianella parviflora (Rubiaceae), after more than 70 years of its original collection—a new record for the flora of Iran - Maroofi, Hosein; Rastegar, Azad (Phytotaxa, 2020)
After a gap of 71 years of its original collection in Iraq, Crucianella parviflora is rediscovered from Kurdistan, Iran. A detailed morphometric treatment of the species is provided here. Its taxonomic relationships with the other related species are discussed as well. Our analyses on the conservation status of C. parviflora based on IUCN criteria and categories ranked it as Vulnerable (VU).